The cost of photoselective vaporization of the prostate compared to transurethral resection of the prostate: Experience in a large public Australian teaching centre. (September 2014) - McCahy, PJ; Cheng, K; Paul, E; Gleeson, J
Objective: The purpose of this study was to compare the cost of photoselective vaporization of the prostate (PVP) with transurethral resection of the prostate (TURP) in the treatment of men with bladder outflow obstruction (BOO). Patients and methods: Men underwent PVP or TURP for clinical BOO or urinary retention. We developed a cost framework to calculate the costs of theatre, recovery and ward time in our publically funded institution and calculated a cost for each procedure including the initial stay and any associated admissions over the first 60 days. These costs were statistically analyzed. Results: A total of 99 men underwent PVP and 97 had TURP. Groups were well matched for age and operative indication. The American Society of Anesthesia (ASA) grade was higher for the PVP group with more taking anticoagulants (36% versus 3.1%). PVP was 74% more expensive (median AUD$4243 vs AUD$2439, p <0.001) than TURP, even in a sub-set analysis excluding the anticoagulated patients. This was because of longer operating time and unavoidable disposable costs. Conclusions: Previous cost studies have all had significant flaws. Using our "bottom up" cost framework suggests that the unavoidable costs of purchasing a laser, single use laser fibers and other paraphernalia will almost always exceed the costs associated with in-patient stay. We caution against establishing a PVP service in a public hospital setting.